2012
DOI: 10.1177/1934578x1200700802
|View full text |Cite
|
Sign up to set email alerts
|

(6R,9S)-6″-(4″-Hydroxybenzoyl)-Roseoside, a New Megastigmane Derivative from Ouratea polyantha and its Effect on Hepatic Glucose-6-phosphatase

Abstract: A new megastigmane derivative, (6R,9S)-6′-(4″-hydroxybenzoil)-roseoside 1 and two known compounds, the biflavone agathisflavone 2 and the carboxylic acid derivative 4-hydroxibenzoic acid 3 were isolated and purified from leaves and stems of Ouratea polyantha Engl. Agathisflavone was isolated in a single high-speed counter-current chromatography run, meanwhile the megastigmane and the carboxylic acid derivatives were purified in two steps, a combination of high-speed countercurrent chromatography and analytical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…13 C‐NMR (CD 3 OD, 100 MHz): δ = 184.3 (C‐4''), 183.95 (C‐4), 166.19 (C‐2''), 166.06 (C‐2), 165.10 (C‐7''), 164.64 (C‐7), 162.79 (C‐4'''), 162.54 (C‐4'), 162.54 (C‐5), 161.28 (C‐5''), 159.05 (C‐9''), 156.90 (C‐9), 129.51 (C‐2'''/6'''), 129.24 (C‐2'/6'), 123.37 (C‐1'''), 123.26 (C‐1'), 117.06 (C‐3'''/5'''), 116.86 (C‐3'/C‐5'), 105.43 (C‐10), 105.18 (C‐10''), 105.09 (C‐6), 103.83 (C‐3''), 103.33 (C‐3), 100.72 (C‐8''), 100.15 (C‐6''), 94.93 (C‐8). These data were confirmed with the related literature (Bermúdez et al., 2012; Chari et al., 1977; Ndongo et al., 2015).…”
Section: Resultssupporting
confidence: 91%
“…13 C‐NMR (CD 3 OD, 100 MHz): δ = 184.3 (C‐4''), 183.95 (C‐4), 166.19 (C‐2''), 166.06 (C‐2), 165.10 (C‐7''), 164.64 (C‐7), 162.79 (C‐4'''), 162.54 (C‐4'), 162.54 (C‐5), 161.28 (C‐5''), 159.05 (C‐9''), 156.90 (C‐9), 129.51 (C‐2'''/6'''), 129.24 (C‐2'/6'), 123.37 (C‐1'''), 123.26 (C‐1'), 117.06 (C‐3'''/5'''), 116.86 (C‐3'/C‐5'), 105.43 (C‐10), 105.18 (C‐10''), 105.09 (C‐6), 103.83 (C‐3''), 103.33 (C‐3), 100.72 (C‐8''), 100.15 (C‐6''), 94.93 (C‐8). These data were confirmed with the related literature (Bermúdez et al., 2012; Chari et al., 1977; Ndongo et al., 2015).…”
Section: Resultssupporting
confidence: 91%
“…The component Roseo isolated from various plants, including A. muricata contained in NA, has a variety of functional activities. It relaxes precontracted aortic rings in an endothelium-dependent manner [29], increases insulin secretion [30], inhibits rat liver microsomal glucose-β-phosphate [31], potentiates the inhibitory activity against angiotensin-converting enzyme, although itself shows no activity against an its enzyme [32], shows inhibitory effects on lipopolysaccharide (LPS)-induced nitric oxide (NO) production in RAW264.7 cells [33], prevents oxidative stress [34], and has a depigmentation effect in melanocytes by inhibiting melanin synthesis [35]. However, it has not been reported yet that Roseo directly suppresses hypertensive effects caused by the upregulation of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…was found to exert hepatoprotective effects, where a reduction in SGOT (also called aspartate aminotransferase [AST]) and an increase in SGPT (also called alanine aminotransferase [ALT]) levels were observed in rats and mice . In another study, this compound was also found to inhibit hepatic glucose‐6‐phosphatase in male Sprague–Dawley rats (Table ).…”
Section: Biological Activities Of Agathisflavonementioning
confidence: 99%